Optimization of Electric Automation Control Model Based on Artificial Intelligence Algorithm. (18th March 2022) - Ma, Run; Kareem, Shahab Wahhab; Kalra, Ashima; Doewes, Rumi Iqbal; Kumar, Pankaj; Miah, Shahajan
Abstract : To effectively solve the problems faced by modern electrical engineering, the design of an electrical automation control system based on artificial intelligence technology is realized. A model of electrical automation control system based on an artificial intelligence algorithm is presented. The control parameters are optimized by using the artificial intelligence algorithm control strategy. The research results show that when there is 20% load interference and 2.1 Hz frequency interference, the maximum failure rate of the turbine under system control is 0.02, indicating that the system has high anti-interference. Therefore, in the automatic control of electrification, the application of the artificial intelligence algorithm can greatly improve the control response time of the automatic control of electrification, save cost, and achieve efficient production.